THE EFFECT OF CONTINUING BUSINESS IN THE INDONESIAN RETAIL SECTOR ON LABOR ABSORPTION - Astuty, Pudji (UNIVERSITAS INDRAPRASTA PGRI, 2023)
The retail industry in Indonesia contributes heavily to the Gross Domestic Product (GDP) and also absorbs a large number of workers. As a developing country, the growth rate of the Indonesian retail industry is influenced by the strength of people's purchasing power, population growth, and also the public's need to satisfy consumer products. The purpose of this study is to analyze the effect of business continuity in the retail sector on employment. The research method used in this study is linear regression with the ordinary least squares method. The results show that the business continuity of the retail sector has a significant and positive effect on employment in Indonesia.